The use of statistical methods for the evaluation of land adjustment proposals and elimination of the patchwork pattern of land ownership - Leń, Przemysław; Skrzypczak, Izabela; Oleniacz, Grzegorz; Mika, Monika (International Conference “Environmental Engineering”, 2017)
The analysis of the need for agricultural land consolidation in villages of the commune of Sławno was performed to identify villages in which adjustment interventions were needed most urgently. The factors indicative of the urgency of land adjustment were selected on the basis of a comprehensive analysis of the natural, social, economic and financial conditions characterizing the investigated villages. The analysis was carried out on the basis of data obtained from the Register of Land and Buildings of the District Office in Opoczno and the Office of the Commune of Sławno. The study allowed us to determine the surface area of land requiring urgent consolidation and exchange, thus providing grounds for applying for funds for the implementation of the proposed land adjustment scheme. Calculations were done on the basis of 19 factors (x1– x19) belonging to five groups of characteristics describing each of the investigated villages. The results expressed in the form of a synthetic measure calculated for each village allowed us to prioritize consolidation interventions. The priority ranking obtained was compared with another ranking performed using the zero unitarization method (ZUM).
Keywords: land consolidation; land exchange; land fragmentation; ranking; statistical methods